A QoE-aware Reinforcement Approach to Disseminate Warning Videos on LTE-VANETs - Quadros, Carlos; Santos, Aldri; Rosário, Denis; Cerqueira, Eduardo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
The wide range of Vehicular Ad-hoc NETwork's (VANETs) applications, e.g., real-time video dissemination, have made VANETs an interesting field of mobile wireless communication. Vehicle-to-Vehicle (V2V) communication enables users to distribute significant amount of real-time video traffic over VANETs and to alleviate congestion over LTE networks. However, the video delivery process considering an adequate Quality of Experience (QoE) in VANETs is a critical issue in both academic and industrial communities due to dynamic network topology, importance of video QoE, and broadcast nature of VANETs. This paper presents a Qoe-Aware Reinforcement approach to disseminate warning videos on LTE-VANETs, called QAR. It enables an enhancement for routing protocols in LTE-VANETs that takes advantage of a centralized architecture around the base station to improve the route management, and to provide video dissemination with QoE support. We analyze the performance of QAR by using NS-2 simulations and a realistic urban mobility model. Results show gains of QAR in comparison to existing proposals, where it achieves video dissemination with QoE support, less routing overhead, and robustness in LTE-VANETs.